Belief Adjustment Model in the Revision of Beliefs: An Experimental Study of the Role of Order Effect and Cognitive Style - Burhanuddin; Yusnaini; Hakiki, Arista (Archives of Business Research, 2023)
This research is an experimental study that aims to examine the role of order effect, cognitive style and information disclosure on investor behavior in decision making. An experimental study was conducted to analyze whether there were differences in investment decisions between participants who were given a series of information on good news followed by bad news (Scenario A) and bad news followed by good news (Scenario B), and to test the interaction between cognitive style and information order. Furthermore, it also analyzes whether there are differences in investment decisions between participants with an analytical versus intuitive cognitive. Participants are 165 undergraduate students majoring in accounting. The result shows that there are differences in investment decisions between participants who receive information either good news followed by bad news or bad news followed by good news in the step-by-step presentation pattern in the long information series. Meanwhile, there was no difference in investment decisions between participants with an analytical and intuitive cognitive style. Thus, cognitive style does not moderate the relationship between the order of evidence and revision of beliefs in investment decision making.